2019
DOI: 10.1111/jre.12683
|View full text |Cite
|
Sign up to set email alerts
|

Impact of natural curcumin on the progression of experimental periodontitis in diabetic rats

Abstract: Objective To evaluate the role of natural curcumin (CURC) on experimental periodontitis (EP) in animals with diabetes mellitus (DM). Material and Methods One hundred rats were assigned to DM + placebo (PLA); DM + CURC; DM + insulin (INS); DM + CURC + INS; and Non‐DM. Diabetes was induced by streptozotocin. After 3 days, they were initiated CURC and PLAC solutions and insulin administrations, daily for 30 days. This included a period of 19 days prior to EP induction (ligature at the first mandibular and the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 58 publications
(138 reference statements)
1
27
0
Order By: Relevance
“…A stock solution of RSV ¶ molecular weight: 228.2) was prepared in Tween-80 # and diluted further in water to obtain a working concentration to provide safe and convenient ingestion volume (1 mL) to dose the animals at a level of 10 mg/kg of RSV. [16][17][18][19][20] The PLAC was prepared with the same volume of Tween-80 and water used in the preparation of RSV. offered daily via gavage.…”
Section: Treatment Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…A stock solution of RSV ¶ molecular weight: 228.2) was prepared in Tween-80 # and diluted further in water to obtain a working concentration to provide safe and convenient ingestion volume (1 mL) to dose the animals at a level of 10 mg/kg of RSV. [16][17][18][19][20] The PLAC was prepared with the same volume of Tween-80 and water used in the preparation of RSV. offered daily via gavage.…”
Section: Treatment Groupsmentioning
confidence: 99%
“…Insulin was administered daily by subcutaneous injection of neutral protamine Hagedorn ‖ diluted in 0.9% NaCl -5.5 to 3.5 mL at 6:00 pm and at 6 am. 20 All treatments (RSV, PLAC, and INS) were performed for 30 days. A period of 19 days before EP induction and then for another 11 days after that also is included.…”
Section: Treatment Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested a positive effect of curcumin on bone formation in diabetes and diabetes-related periodontitis [22]. However, few studies have investigated the effectiveness of natural curcumin on alveolar bone formation in diabetic osteoporosis, and there is also a lack of investigations into cortical bone and cancellous bone.…”
Section: Curcumin Treatment Improved Alveolar Bone Formation In Diabementioning
confidence: 99%
“…More importantly, it is reported that curcumin could suppress osteoclast activities by inhibiting the expression of transcription factor AP-1 [21]. Moreover, curcumin, in combination with insulin, inhibits alveolar bone loss of experimental periodontitis in diabetic rats [22].…”
Section: Introductionmentioning
confidence: 97%